Karakteristik Performa Generator Oxyhydrogen Tipe Dry Cell dengan Penambahan Katalis Kalium Hidroksida - Efendi, Sulkan; Amalia, Rif?ah; Anggun Nurisma, Radina (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The declining petroleum production in Indonesia requires the alternative ofrenewable energy and be more eco- friendly, so it needs more flexible alternative energy. Oneof them is the energy gained from oxyhydrogen gas (Brown Gas). Oxyhydrogen gas can beobtained by breaking down the water molecule (H2O) with the help of electrical energy orcommonly called an electrolisys process. In this study, used oxyhydrogen dry cell generatorstype with 316L stainless steel electrode material consisting of 6 cells with the variation of theKOH catalysts 50, 60, 70, 80, and 90 grams per 1 liter aquadest. The characteristics of theoxyhydrogen generator performance testing are obtained, power consumption, oxyhydrogen gasproduction rate, and oxyhydrogen generator efficiency. From the results of studies that havebeen conducted, it is possible to know that increasing the concentration of KOH catalysts leadsto increased power consumption. The highest electrical energy consumption is 38,94 Watt at theconcentration of the KOH catalyst 90 gr/l and the lowest electrical energy consumption is 21,25Watt at the concentration of the KOH Catalyst 50 gr/l. Then the rate of oxyhydrogen gasproduction is increasing with increasingly high concentrations of KOH catalysts. The highestoxyhydrogen gas production is 9,045e-7 kg/s at the concentration of the 90 gr/l KOH catalystand the lowest oxyhydrogen gas production is 4,522e-7 kg/s at the concentration of the KOHCatalyst 50 gr/L. So the highest oxyhydrogen generator efficiency is 54,76% at the 70 gr/lconcentration of the KOH catalyst.